Effect of Activation of the GLT-1 Transporter by a Beta-Lactam Antibiotic on Serotonin-Induced Scratching Behavior in Mice - Gunduz, O.; Topuz, R.D.; Todurga, Z.G.; Duvan, K.; Karadag, C.H.; Ulugol, A. (Нейрофизиология, 2015)
Glutamate is believed to be the predominant excitatory neurotransmitter in the networks
responsible for itch-related behavior. Beta-lactam antibiotics were shown to exert
neuroprotective effects by increasing expression of the glutamate transporter GLT-1. We
observed whether repeated administration of the beta-lactam antibiotic ceftriaxone suppresses
serotonin-induced itch-related behavior (similarly to its effect on pain transmission) in mice.
Chronic, but not acute, ceftriaxone introductions reduced the number of serotonin-induced
scratches; dihydrokainic acid, a selective GLT-1 transporter inhibitor, partly but significantly
abolished this effect of ceftriaxone. Our findings suggest that GLT-1 activation by beta-lactam
antibiotics looks promising for the treatment of chronic itch. Як вважають, глутамат є основним збуджуючим нейротрансмітером у нейронних мережах, відповідальних за поведінкові моторні прояви при почутті свербіжу. β-лактамні антибіотики мають нейропротективні властивості, оскільки
забезпечують посилену експресію глутаматного транспортера GLT-1. Ми з’ясовували, чи здатне повторне введення
β-лактамного антибіотика цефтриаксону пригнічувати викликані ін’єкціями серотоніну поведінкові моторні прояви (чухальні рухи), пов’язані з індукцією почуття свербіжу (подібно до впливу цього агента на біль) у мишей. Хронічні (але не поодинокі) введення цефтриаксону викликали
зменшення кількості рухів чухання. Селективний блокатор
транспортера GLT-1 дигідрокаїнова кислота частково, але
істотно перешкоджала цьому ефекту цефтриаксону. Наші
спостереження дають підстави вважати, що активація GLT-1
β-лактамними антибіотиками є перспективним підходом у
лікуванні хронічного свербіжу.